Association of mental demands in the workplace with cognitive function in older adults at increased risk for dementia - Zülke, Andrea; Luppa, Melanie; Röhr, Susanne; Weißenborn, Marina; Bauer, Alexander; Samos, Franziska-Antonia Zora; Kühne, Flora; Zöllinger, Isabel; Döhring, Juliane; Brettschneider, Christian; Oey, Anke; Czock, David; et al. (BMC geriatrics, 2021)
Growing evidence suggests a protective effect of high mental demands at work on cognitive function in later life. However, evidence on corresponding associations in older adults at increased risk for dementia is currently lacking. This study investigates the association between mental demands at work and cognitive functioning in the population of the AgeWell.de-trial.
Gesehen am 11.10.2022